Antibody Drug Conjugates in Glioblastoma – Is There a Future for Them? - Parakh, Sagun; Nicolazzo, Joseph; Scott, Andrew M; Gan, Hui Kong (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is an aggressive and fatal malignancy that despite decades of trials has limited therapeutic options. Antibody drug conjugates (ADCs) are composed of a monoclonal antibody which specifically recognizes a cellular surface antigen linked to a cytotoxic payload. ADCs have demonstrated superior efficacy and/or reduced toxicity in a range of haematological and solid tumors resulting in nine ADCs receiving regulatory approval. ADCs have also been explored in patients with brain tumours but with limited success to date. While earlier generations ADCs in glioma patients have had limited success and high toxicity, newer and improved ADCs characterised by low immunogenicity and more effective payloads have shown promise in a range of tumour types. These newer ADCs have also been tested in glioma patients, however, with mixed results. Factors affecting the effectiveness of ADCs to target the CNS include the blood brain barrier which acts as a physical and biochemical barrier, the pro-cancerogenic and immunosuppressive tumor microenvironment and tumour characteristics like tumour volume and antigen expression. In this paper we review the data regarding the ongoing the development of ADCs in glioma patients as well as potential strategies to overcome these barriers to maximise their therapeutic potential.